A COMPARATIVE STUDY OF HEDGING AND BOOSTING DEVICES IN WRITTEN ACADEMIC DISCOURSE - Raxmonova Gulmira Baxrom qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Hedging  and  boosting  strategies  are  very  essential  part  of  written  academic discourse to express writer’s politeness, uncerainty or persuasion. The research argues that hedging and boosting devices are employed frequently for different purposes like expressing  caution,  epistemic  uncertainty  or  presenting  arguments  with  greater certainty and authority. This study investigates the use of hedging and boosting devices in academic discourse in order to identify their linguistic features, pragmatic functions, and frequency of usage.